PENGARUH LAYANAN BIMBINGAN KELOMPOK TERHADAP KESEHATAN MENTAL WARGA BINAAN ANAK (KASUS NON NARKOBA) DI LAPAS ANAK PEKANBARU - Lianti '; Zulfan Saam; Rosmawati ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aimed to determine the effect of group counseling services to the mentally health of inmates of children ( non-drug cases) in pekanbaru child prisons. The method used is pre experimental method using a pattern of the one group pretest-posttest design. Research is done twice: before the experiment(pre-test) and after the experiment (post-test)with a group Subject. Analysis data used in this study qualitative and descriptive analytics quantitative. Subject this study were selected using the technique of non-probability sampling withmethod purposive samplingnumbered 7 inmates children of non drug cases. This research was conducted by providing counseling services as much as 5 times meeting. Analysis group used is Wilcoxon test. The results showed there was no significant effect of group counseling services to the level of Mentally health (obtained Asymp. Sign amounted to 0.658 where 0.658> 0.05).Keywords: Mentally Health, Tutoring Services Group, Citizens Children Patronage